Exploring the Role of Educational Psychology in Enhancing Teachers’ Professional Practice - Mustika Dewi Muttaqien (Journal of Educational Management Research, 2026)
This study aims to examine the contribution of educational psychology and its role in supporting teachers’ professional practice and effective learning processes. The research employed a descriptive analytical method using a library research approach. Data were collected through the analysis of primary and secondary sources, including scholarly journals and books related to psychology, education, and educational psychology. The findings indicate that educational psychology contributes significantly to curriculum development, learning design, student assessment, and the understanding of students’ behavioral characteristics in the teaching and learning process. In addition, educational psychology supports the creation of inclusive learning environments, the development of students’ social and emotional skills, the provision of constructive feedback, the promotion of independent learning, and the implementation of innovative instructional methods. The study also reveals that educational psychology plays an important role in helping teachers address classroom challenges, understand individual differences among students, and develop fair and effective assessment strategies. The implications of this study highlight the importance of integrating educational psychology into teacher professional development to improve teaching quality and student learning outcomes.